Novel 1H-Pyrrole-2,5-dione (maleimide) proxies for the assessment of photic zone euxinia - Naeher, Sebastian; Grice, Kliti (Elsevier Science BV, 2015)
1H-Pyrrole-2,5-diones (maleimides) and 1-alkyl-2,3,6-trimethylbenzenes (aryl isoprenoids), degradation products of tetrapyrrole pigments and carotenoids respectively, were analysed and compared with pristane/phytane (Pr/Ph) ratios to reconstruct past redox conditions in three geologic sections. One section comes from the Middle–Late Devonian and was deposited before the Frasnian–Famennian boundary mass extinction. The two other sections span the Late Permian to the Early Triassic as well as the Late Triassic to the Early Jurassic, and recorded the Permian–Triassic (P/T) and Triassic–Jurassic (T/J) extinction events respectively. The 2-methyl-3-isobutyl-maleimide (Me,i-Bu maleimide) to 2-methyl-3-ethyl-maleimide (Me,Et maleimide) and 2-methyl-3-npropyl- maleimide (Me,n-Pr maleimide) to Me,Et maleimide ratios (Me,i-Bu/Me,Et and Me,n-Pr/Me,Et ratios) in the studied sections revealed amoderate to strong negative correlation to the aryl isoprenoid ratio (AIR), defined as (C13–C17 1-alkyl-2,3,6-trimethylbenzenes)/(C18–C22 1-alkyl-2,3,6-trimethylbenzenes), indicating that these maleimide ratios can be used as robust, specific indicators of photic zone euxinia (PZE). These results agreed with Pr/Ph ratios, which were used as diagnostic indicators to differentiate between oxic and anoxic conditions. In agreement with previous studies, the novel maleimide proxies suggest that all three mass extinctions werelargely characterised by PZE depositional conditions.